Pandemic Preparedness: The Potential Advantage of Medicines That Prevent Acute Side Effects of Vaccination, SARS-CoV-2 as an Example - Pantea Kiani; Jessica Balikji; Johan Garssen; Joris C. Verster (Future Pharmacology, 2022)
Vaccination against SARS-CoV-2 is an important and essential strategy to combat the 2019 coronavirus disease (COVID-19) pandemic. Vaccination has shown to be effective in reducing the spread of SARS-CoV-2, reducing the chances of becoming infected and developing severe COVID-19, and reducing hospitalization and mortality rates. However, the vaccinations against SARS-CoV-2 are accompanied by undesirable side effects which may be in part responsible for a reduction in the willingness to become vaccinated. At this moment (June 2022), 24.3% of the US adult population (18+ years old) is not fully vaccinated against SARS-CoV-2, and 49.5% did not receive their follow-up booster vaccination. The most important motives for refusing vaccination are the unknown long-term side effects and the known acute side effects of vaccination. Here, we discuss the importance of recognizing the impact of this reactogenicity on individuals’ willingness to vaccinate and how the development of effective and safe medicines that prevent or mitigate the unwanted side effects of the vaccination may help to increase the willingness to vaccinate.